Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1519/jsc.0b013e31824eddda
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of the Karate-Specific Aerobic Test

Abstract: ABThe aim of this study was to examine absolute and relative reliabilities and external responsiveness of the Karate-specific aerobic test (KSAT). This study comprised 43 male karatekas, 19 of them participated in the first study to establish test-retest reliability and 40, selected on the bases of their karate experience and level of practice, participated in the second study to identify external responsiveness of the KSAT. The latter group was divided into 2 categories: national-level group (G(n)) and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 26 publications
5
48
1
1
Order By: Relevance
“…The present study aimed to evaluate the physiological and biomechanical behavior during the induced fatigue protocol in karate. The physiological response shows that the heart rate peak was greater than the found by Chaabéne et al [4,5]. Similar values to the anaerobic threshold were found in situation of simulated combat [4,17,18].…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The present study aimed to evaluate the physiological and biomechanical behavior during the induced fatigue protocol in karate. The physiological response shows that the heart rate peak was greater than the found by Chaabéne et al [4,5]. Similar values to the anaerobic threshold were found in situation of simulated combat [4,17,18].…”
Section: Discussionsupporting
confidence: 79%
“…The cortisol and lactate increases were also higher than in combat simulation [3,5,20], kumite karate training or in competition event [16]. When evaluated 9 elite-level male karatekas in combat situation in Tunisia, Chaabene [27] identified double of cortisol values post combat, when compared to the pre-combat situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was also reported by Ravier et al [24] and, in a recent review, Chaabene et al [7] confirmed that V.O 2 max does not seem to be influenced by the karate practice level. However, these same authors [8] recently showed that the time to exhaustion during a karate-specific aerobic test was significantly shorter in regional-level karatekas (841 ± 134 s) than in national-level karatekas (1032 ± 101 s). This result highlights the importance of using a karatespecific test to differentiate between practice levels rather than a graded exercise test on a treadmill, as proposed in the present study or by Ravier et al [24].…”
Section: Discussionmentioning
confidence: 99%